ITGB1 as a prognostic biomarker correlated with immune suppression in gastric cancer - Wenchao Gu; Hui Sun; Meng Zhang; Shaocong Mo; Cong Tan; Shujuan Ni; Zongcheng Yang; Yulin Wang; Weiqi Sheng; Lei Wang (Cancer Medicine, 2023)
Abstract Introduction Gastric cancer is one of the common malignant tumors with a high incidence and mortality in China. Prognostic biomarkers and potential predictors of the treatment efficacy of gastric cancer urgently need to be identified. Integrin‐β (ITGB) is a superfamily of integrins and is involved in cell adhesion, tissue repair, immune response, and tumor metastasis. Methods We analyzed ITGB1 expression in our hospital samples of the gastric cancer cohort. And the public data of The Cancer Genome Atlas stomach adenocarcinoma (TCGA‐STAD), The Asian Cancer Research Group (ACRG)/GSE62254, and GSE15459 data sets were analyzed by using the bioinformatic methods. The relationships between ITGB1 expression and clinicopathological features, patient prognosis, activation of the Wnt/β‐catenin signaling pathway, and tumor immunosuppressive factors were also explored. Results The positive rate of ITGB1 expression in the Fudan University Shanghai Cancer Center gastric cancer tumor tissues was 61.4% (258/420) and correlated with deep invasion (p = 0.017), an advanced clinical stage (p = 0.011), and a poor prognosis (p < 0.05). The TCGA‐STAD/ACRG/GSE15459 cohorts also showed similar results. ITGB1 is one of the upstream molecules of the Wnt/β‐catenin signaling pathway and is correlated with tumor immune suppression. In gastric cancer, we found a correlation between ITGB1 expression and Wnt/β‐catenin signaling pathway activity. In the TCGA‐STAD/ACRG/GSE15459 cohorts, ITGB1 expression was positively associated with immunosuppressive factors and negatively associated with immunoactive factors. Patients with low ITGB1 expression exhibited a significantly high immunotherapy response ratio according to an analysis of tumor immune dysfunction and exclusion (TIDE), which may indicate that ITGB1 is a potential predictor of immunotherapy efficacy. Conclusions ITGB1 affects the prognosis in gastric cancer patients and plays a core role in immune suppression in gastric cancer.